Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cells11050799
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cell Recovery: Freezing and Thawing Optimization of Induced Pluripotent Stem Cells

Abstract: Achieving good cell recovery after cryopreservation is an essential process when working with induced pluripotent stem cells (iPSC). Optimized freezing and thawing methods are required for good cell attachment and survival. In this review, we concentrate on these two aspects, freezing and thawing, but also discuss further factors influencing cell recovery such as cell storage and transport. Whenever a problem occurs during the thawing process of iPSC, it is initially not clear what it is caused by, because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…They grew exponentially (in exponential phase) while P2D11 cells had entered a deceleration phase, and P2D28 had almost no proliferation. Previous studies have shown that induced pluripotent stem cells (iPSC) were also found to be best cryopreserved at the exponential growth phase [37]. We therefore hypothesized that exponential phase was the optimal growth phase for RPE cryopreservation and then addressed this hypothesis by comparison of the recovery rate, viability rate and attachment rate for cells frozen at different phases of the growth.…”
Section: Discussionmentioning
confidence: 99%
“…They grew exponentially (in exponential phase) while P2D11 cells had entered a deceleration phase, and P2D28 had almost no proliferation. Previous studies have shown that induced pluripotent stem cells (iPSC) were also found to be best cryopreserved at the exponential growth phase [37]. We therefore hypothesized that exponential phase was the optimal growth phase for RPE cryopreservation and then addressed this hypothesis by comparison of the recovery rate, viability rate and attachment rate for cells frozen at different phases of the growth.…”
Section: Discussionmentioning
confidence: 99%
“…They are of potential use as therapeutics in tissue regeneration (e.g., neural or ocular regeneration) and in disease modeling to study the pathology of diseases at a cellular level [ 139 ]. Procedures for cryopreservation of iPSCs usually fall into two categories: slow cooling or vitrification, and further it is of importance to distinguish between freezing of single cells or cell aggregates and the exact mode of freezing and thawing [ 140 , 141 ].…”
Section: Other Common Cellular Therapeuticsmentioning
confidence: 99%
“…In cryopreservation facilities, it has been reported that the microbial load should be controlled before freezing sperm in order to prevent cross-contamination in liquid nitrogen [172]. Freezing sperm from brood stocks that are not infected or have the least pathogen in their sperm will be the best solution.…”
Section: Suggestionsmentioning
confidence: 99%